Feldspar crystal containing divalent copper ions and method for producing the same
Patent Information
- Application Number
- CN202210467715.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-04-29
AI Technical Summary
但是,目前一直没有办法在长石晶体中得到二价铜离子
[0013] This invention offers the following advantages: Currently, copper diffusion into feldspar crystals at high temperatures can only occur as cuprous ions. These cuprous ions, diffusing into the feldspar crystal at high temperatures, spontaneously capture the hot electrons generated by the feldspar crystal and are reduced to zero-valent copper. This invention, by introducing lithium ions into the feldspar crystal through diffusion, successfully achieves the transformation from cuprous ions to divalent copper ions within the feldspar crystal, thereby successfully preparing feldspar crystals containing divalent copper ions.
Smart Images

Figure CN117005027B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ion doping technology for crystal materials, and particularly to a feldspar crystal containing divalent copper ions and its preparation method. Background Technology
[0002] Oxygen, silicon, and aluminum are the three most abundant elements on Earth. Aluminosilicate mineral crystals composed of these three elements are abundant on Earth. Among them, aluminosilicate materials, represented by zeolites, have undergone a process from discovery as natural minerals to large-scale synthesis and application as artificial materials. Recently, a naturally occurring labradorite crystal, which also belongs to the category of aluminosilicate materials, has attracted special attention. Researchers have discovered copper nanoparticles in a small amount of naturally occurring labradorite crystals, indicating the potential of labradorite crystals in the preparation of copper-doped materials. Therefore, studying the diffusion of copper in this natural mineral crystal is of great significance for its subsequent large-scale application.
[0003] Regarding the diffusion of copper in feldspar crystals, current research suggests that cuprous ions can be introduced into feldspar crystals through high-temperature diffusion. Once inside the crystal, these cuprous ions can further capture the hot electrons generated by the feldspar crystal at high temperatures, reducing it to zero valence. However, it has been impossible to obtain divalent copper ions in feldspar crystals. This invention discloses a feldspar crystal containing divalent copper ions and its preparation method. By adding a lithium-containing component to the diffusion raw material, the process of cuprous ions capturing hot electrons and becoming zero-valent copper during high-temperature diffusion is broken. This transforms the cuprous ions diffused into the feldspar crystal at high temperatures into divalent copper ions. The feldspar crystal containing divalent copper ions exhibits a captivating blue-green color, possessing significant application value in jewelry materials and colored pigments. Summary of the Invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art, and has invented a feldspar crystal containing divalent copper ions and a method for preparing the same.
[0005] According to embodiments of the present invention, the feldspar crystal containing divalent copper ions comprises a feldspar crystal and divalent copper ions and lithium ions doped into the feldspar crystal. The mass concentration of divalent copper ions (based on elemental composition) in the feldspar crystal is 0.001-2%, and the mass concentration of lithium ions in the feldspar crystal is 0.002-4%. The feldspar crystal is one of albite, orthoclase, andesite, labradorite, terfeldspar, anorthoclase, orthoclase, orthoclase, orthoclase.
[0006] According to an embodiment of the present invention, a method for preparing feldspar crystals containing divalent copper ions includes the following steps: 1) Prepare the diffusion raw materials and transfer them to a crucible; 2) Transfer the feldspar crystals into the diffusion material to ensure that the feldspar crystals can come into direct contact with the diffusion material; 3) Place the crucible containing the diffusion material and feldspar crystals into a heating device for high-temperature heat treatment.
[0007] According to an embodiment of the present invention, the diffusion raw material includes a substance component X containing copper, a substance component Y containing lithium, and a dispersant; The mass concentration of copper-containing component X in the diffusion raw material is 0.01-10%, the mass concentration of lithium-containing component Y in the diffusion raw material is 0.02-10%, and the mass ratio of the dispersant to the feldspar crystals is (0.01-100):1.
[0008] According to an embodiment of the present invention, the copper-containing component X is selected from one or more of copper, copper-containing alloys, and copper compounds; The lithium-containing component Y is selected from one or more lithium-containing alloys and lithium compounds; The dispersant is selected from one or more of zirconium oxide, silicon oxide, calcium oxide, zinc oxide, and magnesium oxide.
[0009] According to an embodiment of the present invention, the diffusion raw material further comprises a reducing substance; The reducing substance is selected from one or more of stannous oxide, ferrous oxide, antimony trioxide, activated carbon, and graphite; The molar ratio of the reducing substance to the copper-containing component X is (0-20):1.
[0010] According to an embodiment of the present invention, the temperature range of the high-temperature heat treatment is 1050-1500℃.
[0011] According to an embodiment of the present invention, the high-temperature heat treatment time is 1 to 720 hours.
[0012] According to an embodiment of the present invention, the feldspar crystal is selected from one of albite crystal, orthoclase crystal, andesine crystal, labradorite crystal, bainite crystal, anorthoclase crystal, orthoclase crystal, and sansine crystal.
[0013] This invention offers the following advantages: Currently, copper diffusion into feldspar crystals at high temperatures can only occur as cuprous ions. These cuprous ions, diffusing into the feldspar crystal at high temperatures, spontaneously capture the hot electrons generated by the feldspar crystal and are reduced to zero-valent copper. This invention, by introducing lithium ions into the feldspar crystal through diffusion, successfully achieves the transformation from cuprous ions to divalent copper ions within the feldspar crystal, thereby successfully preparing feldspar crystals containing divalent copper ions. Attached Figure Description
[0014] Figure 1 This is a flowchart of a method for preparing feldspar crystals containing divalent copper ions. Figure 2 The appearance of feldspar crystals containing divalent copper ions obtained by high-temperature diffusion treatment in Example 1 of this invention; Figure 3 The ultraviolet-visible absorption spectrum of feldspar crystals containing divalent copper ions obtained by high-temperature diffusion treatment in Example 1 of this invention; Figure 4 The fluorescence spectrum of feldspar crystals containing divalent copper ions obtained by high-temperature diffusion treatment in Example 1 of this invention; Figure 5 The appearance of the feldspar crystals obtained by high-temperature diffusion treatment in Comparative Example 1; Figure 6 The ultraviolet-visible absorption spectrum of the feldspar crystals obtained by high-temperature diffusion treatment in Comparative Example 1 is shown. Figure 7 The fluorescence spectrum of the feldspar crystals obtained by high-temperature diffusion treatment in Comparative Example 1 is shown. Figure 8 The ultraviolet-visible absorption spectrum of feldspar crystals containing divalent copper ions obtained after high-temperature diffusion treatment in Example 2 of this invention; Figure 9 The image shows the ultraviolet-visible absorption spectrum of feldspar crystals containing divalent copper ions obtained after high-temperature diffusion treatment in Example 3 of this invention. Detailed Implementation
[0015] To enable those skilled in the art to better understand the technical solution of the present invention, the feldspar crystals containing divalent copper ions and their preparation method disclosed in the present invention will be described in detail below with reference to the accompanying drawings.
[0016] Figure 1 This is a flowchart of the preparation method of feldspar crystals containing divalent copper ions mentioned in this invention, as shown below. Figure 1As shown, the first step is to prepare the corresponding diffusion material according to the formula. The three components of the diffusion material are weighed and transferred to a mortar for grinding, thereby mixing the diffusion material evenly. The second step is to transfer the evenly mixed diffusion material to a crucible. The crucible is selected according to the high-temperature heat treatment temperature. For example, the material used in this invention is a corundum crucible with a maximum treatment temperature of 1700℃. The third step is to transfer the feldspar crystals to the crucible containing the diffusion material. Depending on different treatment requirements, the feldspar crystals can be selectively buried entirely in the diffusion material, or only a portion of the feldspar crystals can be in contact with the diffusion material. Especially when the mass of the diffusing agent in the diffusion material is relatively small, only a small portion of the feldspar crystals can be ensured to be in contact with the diffusion material. In this treatment method, since the exposed part will not be damaged during the high-temperature heat treatment, the feldspar crystals can be processed and cut into the desired shape according to the actual application scenario before high-temperature heat treatment.
[0017] According to an embodiment of the present invention, the diffusion raw material includes a copper-containing component X, a lithium-containing component Y, and a dispersant. The dispersant is selected from one or more of zirconium oxide, silicon oxide, calcium oxide, zinc oxide, and magnesium oxide. All dispersants are selected from high-melting-point oxides with melting points exceeding 1700°C. Using high-melting-point oxides as dispersants ensures that this portion of the diffusion raw material remains solid during high-temperature processing, thereby reducing contamination and damage to the feldspar crystal surface caused by the diffusion raw material. The mass concentration of copper-containing component X in the diffusion raw material is 0.01-10%, and the mass concentration of lithium-containing component Y in the diffusion raw material is 0.02-10%. Generally, the mass concentration of copper-containing component X in the diffusion raw material is higher than the concentration of divalent copper ions (elementally) in the feldspar crystal to be prepared, thereby ensuring the diffusion rate. The molar ratio between copper-containing component X and lithium-containing component Y can be adjusted as needed. However, the diffusion rate of lithium in feldspar crystals is higher than that of copper, and the temperature at which lithium begins to diffuse efficiently in feldspar crystals is also lower than that of copper. Therefore, the molar concentration of copper in the diffusion raw material is usually higher than that of lithium to ensure a balance between the copper and lithium concentrations diffused into the feldspar crystals. The mass ratio of dispersant to feldspar crystal is (0.01-100):1. If it is necessary to completely encapsulate the feldspar crystal, the mass of dispersant can be increased accordingly. Conversely, if the feldspar crystal only needs to partially contact the diffusion raw material, the amount of dispersant can be reduced, thus lowering the cost of the diffusion process.
[0018] According to embodiments of the present invention, the copper-containing component X is selected from one or more of copper, copper-containing alloys, and copper compounds. The function of the copper-containing component X is to provide a source of cuprous ions. Regardless of the raw material composition used, cuprous ions will begin to be generated in the diffusion material when a high-temperature processing temperature above 1050°C is reached. For example, when the added copper-containing component X is copper powder, during the heating process from room temperature to 1050°C, the copper powder will first be oxidized to copper oxide, and the copper oxide will gradually transform into cuprous oxide at 1050°C. The lithium-containing component Y is selected from one or more of lithium-containing alloys and lithium compounds. The function of the lithium-containing component is to provide a source of lithium ions.
[0019] According to an embodiment of the present invention, the diffusion raw material may further include a reducing agent. According to an embodiment of the present invention, the reducing agent is selected from one or more of stannous oxide, ferrous oxide, antimony trioxide, activated carbon, and graphite. Adding a reducing agent can further control the diffusion process of cuprous ions in the feldspar crystals. According to an embodiment of the present invention, the molar ratio of the reducing agent to the copper-containing component X is (0-20):1.
[0020] According to embodiments of the present invention, the temperature range of the high-temperature heat treatment is 1050-1500℃. The high-temperature heat treatment temperature depends on the type of feldspar crystal used; different feldspar crystals have different solidus temperatures, and the high-temperature heat treatment temperature cannot exceed the solidus temperature of the selected feldspar crystal. According to embodiments of the present invention, the high-temperature heat treatment time is 1-720 hours. As the high-temperature heat treatment time increases, the depth of divalent copper ions obtained in the feldspar crystal also increases. According to embodiments of the present invention, the high-temperature heat treatment can be carried out in an air atmosphere or an inert gas atmosphere; both atmospheres can achieve the diffusion of cuprous ions and lithium ions in the feldspar crystal.
[0021] According to an embodiment of the present invention, in this step, the feldspar crystals include albite crystals, orthoclase crystals, mesoclase crystals, labradorite crystals, terbinite crystals, anorthoclase crystals, orthoclase crystals, and sanshoite crystals. Let Ab represent albite, An represent anorthoclase, and Or represent orthoclase (potassium feldspar), then the solid solution formed by albite and anorthoclase includes albite crystals (Ab...). 90-100% An 0-10% ), austenite crystals (Ab 70-90% An 10-30% ), andesite crystals (Ab 50-70% An 30-50% Labradorite crystals (Ab) 30-50% An 50-70% ), Abretite crystals (Ab 10-30% An 70-90%), anorthite crystals (Ab 0-10% An 90-100% The solid solution formed by albite and potassium feldspar contains sansine crystals.
[0022] The present invention will be described below through specific embodiments. It should be noted that the specific embodiments below are for illustrative purposes only and do not limit the scope of the present invention in any way. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention. In addition, unless otherwise specified, methods that do not specifically describe conditions or steps are conventional methods, and the reagents and materials used are commercially available.
[0023] Example 1: Preparation method of labradorite crystals containing divalent copper ions (1) Weigh 5g of diffusion raw materials zirconium oxide powder, 0.3g of copper oxide powder and 0.1g of lithium oxide powder, put them in an agate mortar and mix them evenly, and then transfer them to a corundum crucible. (2) Transfer a nearly colorless and transparent labradorite crystal (1.5g) to a crucible and embed 1 / 4 of the labradorite crystal in a pre-mixed and uniformly distributed diffusion material; (3) The corundum crucible filled with diffusion material and labradorite crystals was placed in a high-temperature tube furnace and heated to 1150℃ for 3 hours. After diffusion, it was cooled to room temperature and removed, yielding labradorite crystals containing divalent copper ions that were blue-green in color and had an appearance similar to... Figure 2 As shown. The UV-Vis absorption spectra of this sample were measured before and after the high-temperature diffusion treatment, as shown. Figure 3 As shown, after high-temperature diffusion treatment, there is a characteristic absorption peak of divalent copper ions near 750 nm. Figure 4 To test the fluorescence spectrum of the labradorite crystals after high-temperature diffusion, the diffused feldspar crystals did not exhibit a strong fluorescence peak for cuprous ions. Laser exfoliation-inductively coupled plasma mass spectrometry (LASIK-MS) was used to analyze the high-temperature diffused labradorite crystals. The content of divalent copper ions (elementally) in the labradorite crystals was 2990 ppmw, and the content of lithium ions (elementally) was 10764 ppmw.
[0024] Comparative Example 1: (1) Weigh 5g of diffusion raw material zirconia powder and 0.3g of copper oxide powder, put them in an agate mortar and mix them evenly, and then transfer them to a corundum crucible; (2) Transfer a nearly colorless and transparent labradorite crystal (1.5g) to a crucible and embed 1 / 4 of the labradorite crystal in a pre-mixed and uniformly distributed diffusion material; (3) The corundum crucible filled with diffusion material and labradorite crystals was placed in a high-temperature tube furnace and heated to 1150℃ for 3 hours. After diffusion, it was cooled to room temperature and removed. The resulting labradorite crystals containing cuprous ions and copper nanoparticles were red and had the appearance of... Figure 5 As shown. The UV-Vis absorption spectra of this sample were measured before and after the high-temperature diffusion treatment, as shown. Figure 6 As shown, after high-temperature diffusion treatment, there is a characteristic absorption peak of copper nanoparticles near 586 nm. Figure 7 To test the fluorescence spectrum of the labradorite crystals after high-temperature diffusion, strong fluorescence peaks of cuprous ions were observed at 395 nm and 555 nm. Laser ablation-inductively coupled plasma mass spectrometry (LC-MS) was used to analyze the high-temperature diffusion of the labradorite crystals, revealing a copper content of 3203 ppmw.
[0025] Example 2: Preparation method of andesite crystals containing divalent copper ions (1) Weigh 5g of diffusion raw materials zirconium oxide powder, 0.02g of copper oxide powder and 0.005g of lithium oxide powder, put them in an agate mortar and mix them evenly, and then transfer them to a corundum crucible. (2) Transfer a piece of pale yellow transparent andesite crystal (2.1g) into a crucible and embed the entire andesite crystal in the pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and labradorite crystals was placed in a high-temperature tube furnace and heated to 1100℃ for 6 hours. After diffusion, it was cooled to room temperature and removed, yielding blue-green andesite crystals containing divalent copper ions. Figure 8 As shown, a characteristic absorption peak of divalent copper ions is observed near 750 nm after high-temperature diffusion treatment. The labradorite crystals after high-temperature diffusion were analyzed using laser ablation-inductively coupled plasma mass spectrometry (LAS-MS). The content of divalent copper ions (elementally) in the labradorite crystals was 2140 ppmw, and the content of lithium ions (elementally) was 5749 ppmw.
[0026] Example 3: Preparation method of andesite crystals containing divalent copper ions (1) Weigh 0.5g of diffusion raw materials zirconium oxide powder, 0.05g of copper oxide powder and 0.009g of lithium oxide powder, place them in an agate mortar and mix them evenly, then transfer them to a corundum crucible; (2) Transfer a piece of pale yellow transparent medium crystal (3.2g) into a crucible and bring one end of the medium andesite crystal into contact with the pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and andesite crystals was placed in a high-temperature tube furnace and heated to 1100℃ for 12 hours. After diffusion, it was cooled to room temperature and removed, yielding andesite crystals containing divalent copper ions, which were blue-green in color. Figure 9 As shown, a characteristic absorption peak of divalent copper ions is observed near 750 nm after high-temperature diffusion treatment. The andesite crystals after high-temperature diffusion were analyzed using laser ablation-inductively coupled plasma mass spectrometry (ICP-MS). The content of divalent copper ions (elementally) in the andesite crystals was 3321 ppmw, and the content of lithium ions (elementally) was 12109 ppmw.
[0027] Example 4: Preparation method of orthoclase crystals containing divalent copper ions (1) Weigh 5g of silica powder, 0.3g of copper powder and 0.11g of lithium hydroxide powder, place them in an agate mortar and mix them evenly, then transfer them to a corundum crucible. (2) Transfer one piece of austenite crystal (1.5g) to a crucible and embed the austenite crystal completely in the pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and austenite crystals was placed in a high-temperature box furnace and heated to 1050℃ for 1 hour. After diffusion, it was cooled to room temperature and removed, and the austenite crystals containing divalent copper ions were obtained, which were blue-green. The austenite crystals after high-temperature diffusion were tested by laser ablation-inductively coupled plasma mass spectrometry. The content of divalent copper ions (based on elemental composition) in the austenite crystals was 236 ppmw, and the content of lithium ions (based on elemental composition) was 1109 ppmw.
[0028] Example 5: Preparation method of albite crystals containing divalent copper ions (1) Weigh 5g of magnesium oxide powder, 0.0005g of cuprous iodide powder and 0.001g of lithium carbonate powder, place them in an agate mortar and mix them evenly, then transfer them to a corundum crucible. (2) Transfer one piece of albite crystal (1.2g) to a crucible and embed the albite crystal completely in the pre-mixed diffusion material; (3) The corundum crucible containing the diffusion material and albite crystals was placed in a high-temperature tube furnace and heated to 1050℃ for 1 hour. After diffusion, it was cooled to room temperature and removed, and the albite crystals containing divalent copper ions were obtained, which were slightly blue-green. The albite crystals after high-temperature diffusion were tested by laser ablation-inductively coupled plasma mass spectrometry. The content of divalent copper ions (based on elemental composition) in the albite crystals was 12 ppmw, and the content of lithium ions (based on elemental composition) was 26 ppmw.
[0029] Example 6: Preparation method of bainite crystals containing divalent copper ions (1) Weigh 5g of zinc oxide powder, 0.005g of copper-tin alloy powder (Cu50%), and 0.001g of lithium oxide powder, place them in an agate mortar and mix them evenly, then transfer them to a corundum crucible. (2) Transfer one piece of bainite crystal (0.8g) to a crucible and make one side of the bainite crystal contact with the pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and feldspar crystals was placed in a high-temperature tube furnace and heated to 1320℃ for 60 h. After diffusion, it was cooled to room temperature and removed, and the feldspar crystals containing divalent copper ions were obtained, which were blue-green. The feldspar crystals after high-temperature diffusion were tested by laser ablation-inductively coupled plasma mass spectrometry. The content of divalent copper ions (calculated as elements) in the feldspar crystals was 1532 ppmw, and the content of lithium ions (calculated as elements) was 20764 ppmw.
[0030] Example 7: Preparation method of anorthite crystals containing divalent copper ions (1) Weigh 5g of diffusion raw material zirconium oxide powder, 0.025g of cuprous chloride powder and 0.17g of lithium aluminum alloy powder, put them in an agate mortar and mix them evenly, and then transfer them to a corundum crucible. (2) Transfer one piece of anorthite (4.1g) to a crucible and embed half of the anorthite crystal in a pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and anorthite crystals was placed in a high-temperature tube furnace and heated to 1500℃ for 720h. After diffusion, it was cooled to room temperature and removed, and the anorthite crystals containing divalent copper ions were obtained, which were dark green. The anorthite crystals after high-temperature diffusion were tested by laser ablation-inductively coupled plasma mass spectrometry. The content of divalent copper ions (based on elemental composition) in the anorthite crystals was 18991ppmw, and the content of lithium ions (based on elemental composition) was 37764ppmw.
[0031] Example 8: Preparation method of orthoclase crystals containing divalent copper ions (1) Weigh 0.1g of zirconium oxide powder, 0.002g of cuprous oxide powder and 0.001g of lithium oxide powder, place them in an agate mortar and mix them evenly, then transfer them to a corundum crucible. (2) Transfer one piece of orthoclase crystal (3.3g) into a crucible and bring one end of the orthoclase crystal into contact with the pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and orthoclase crystals was placed in a high-temperature tube furnace and heated to 1050℃. Under nitrogen atmosphere, it was heat-treated for 10 hours. After diffusion, it was cooled to room temperature and removed. The orthoclase crystals containing divalent copper ions were obtained and were blue-green. The orthoclase crystals after high-temperature diffusion were tested by laser ablation-inductively coupled plasma mass spectrometry. The content of divalent copper ions (based on elemental composition) in the orthoclase crystals was 1681 ppmw, and the content of lithium ions (based on elemental composition) was 9868 ppmw.
[0032] Example 9: Preparation method of orthoclase crystals containing divalent copper ions (1) Weigh 50g of diffusion raw materials, 2.5g of copper oxide powder and 1.15g of lithium carbonate powder, put them in a mortar and mix them evenly, and then transfer them to a corundum crucible. (2) Transfer 5 pieces of sanspar crystal (total 10.3g) to a crucible and make one side of the sanspar crystal contact with the pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and orthoclase crystals was placed in a high-temperature tube furnace and heated to 1080℃. It was then heat-treated at high temperature for 24 hours under an argon atmosphere. After diffusion, it was cooled to room temperature and removed. The orthoclase crystals containing divalent copper ions were obtained and were blue-green. The orthoclase crystals after high-temperature diffusion were tested by laser ablation-inductively coupled plasma mass spectrometry. The content of divalent copper ions (calculated as elements) in the orthoclase crystals was 6910 ppmw, and the content of lithium ions (calculated as elements) was 20782 ppmw.
[0033] Example 10: Preparation method of labradorite crystals containing divalent copper ions (1) Weigh 5g of diffusion raw materials: zirconium oxide powder, 0.25g of copper oxide powder, 0.04g of lithium oxide powder, and 0.5g of graphite powder. Mix them evenly in an agate mortar and then transfer them to a corundum crucible. (2) Transfer one piece of labradorite crystal (3.5g) to a crucible and embed the labradorite crystal completely in the pre-mixed diffusion material; (3) The corundum crucible filled with diffusion material and labradorite crystals was placed in a high-temperature tube furnace and heated to 1100℃ for 240h. After diffusion, the sample was cooled to room temperature and removed. The surface of the sample was then simply polished to obtain labradorite crystals containing divalent copper ions, which were blue-green. The labradorite crystals after high-temperature diffusion were tested by laser ablation-inductively coupled plasma mass spectrometry. The content of divalent copper ions (calculated as elements) in the labradorite crystals was 14190ppmw, and the content of lithium ions (calculated as elements) was 27644ppmw.
Claims
1. A method for preparing feldspar crystals containing divalent copper ions, characterized in that, Includes the following steps: 1) Prepare the diffusion raw material and transfer it to a crucible; the diffusion raw material includes a copper-containing component X, a lithium-containing component Y, and a dispersant; the mass concentration of the copper-containing component X in the diffusion raw material is 0.01-10%, the mass concentration of the lithium-containing component Y in the diffusion raw material is 0.02-10%, and the mass ratio of the dispersant to the feldspar crystals is (0.01-100):1; 2) Transfer the feldspar crystals into the diffusion material to ensure that the feldspar crystals can come into direct contact with the diffusion material; 3) Place the crucible containing the diffusion material and feldspar crystals into a heating device for high-temperature heat treatment. The temperature range of the high-temperature heat treatment is 1050-1500℃, and the time of the high-temperature heat treatment is 1-720h. The obtained feldspar crystals containing divalent copper ions have a mass concentration of 0.001-2% in the feldspar crystals and a mass concentration of 0.002-4% in the feldspar crystals.
2. The preparation method according to claim 1, characterized in that, The copper-containing component X is selected from one or more of copper, copper alloys, and copper compounds. The lithium-containing component Y is selected from one or more lithium-containing alloys and lithium compounds. The dispersant is selected from one or more of zirconium oxide, silicon oxide, calcium oxide, zinc oxide, and magnesium oxide.
3. The method according to claim 1, characterized in that, The diffusion raw material further includes reducing substances; The reducing agent is selected from one or more of stannous oxide, ferrous oxide, antimony trioxide, activated carbon, and graphite.
4. The method according to claim 1, characterized in that, The feldspar crystals are selected from one of the following: albite crystals, orthoclase crystals, andesine crystals, labradorite crystals, bainite crystals, anorthoclase crystals, orthoclase crystals, and sansine crystals.
Citation Information
Patent Citations
Method for growing nano material in feldspar crystals
CN112226818A
Method for growing copper nano materials in feldspar crystals
CN112453419A